Sufficiency in the optimal stopping problems - Grigelionis, B. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Григелионис. Достаточность в задачах оптимальной остановкиB. Grigelionis. Pakankamumas optimalaus sustabdymo uždaviniuose